Enlarging Vertebral Body Pneumatocysts in the Cervical Spine - Kitagawa, Tomoaki; Fujiwara, Atsushi; Tamai, Kazuya; Kobayashi, Naoki; Saiki, Kazuhiko; Omata, Sadatoshi; Saotome, Koichi (American Journal of Neuroradiology, 2003)
Summary: An intravertebral pneumatocyst is a relatively rare condition, and its natural course and etiology are unclear. We report a case of intravertebral pneumatocysts in the C5 vertebra that gradually enlarged during a 16-month period as documented by follow-up CT. In addition, direct communication was observed between the gas in the intervertebral disk and another pneumatocyst in the C6 vertebral body, which suggests that the gas in the pneumatocyst had an association with the gas in the degenerated intervertebral disk.